Optical basicity and electronic polarizability of zinc borotellurite glass doped La3+ ions - Mohamed Kamari, Halimah; Mohd Fudzi, Faznny; Abd Azis, Muhammad Noorazlan; Ab. Aziz, Sidek (Elsevier, 2017)
Zinc borotellurite glasses doped with lanthanum oxide were successfully prepared through melt-quenching technique. The amorphous nature of the glass system was validated by the presence of a broad hump in the XRD result. The refractive index of the prepared glass samples was calculated by using the equation proposed by Dimitrov and Sakka. The theoretical value of molar refraction, electronic polarizability, oxide ion polarizability and metallization criterion were calculated by using Lorentz-Lorenz equation. Meanwhile, expression proposed by Duffy and Ingram for the theoretical value of optical basicity of multi-component glasses were applied to obtain energy band gap based optical basicity and refractive index based optical basicity. The optical basicity of prepared glasses decreased with the increasing concentration of lanthanum oxide. Metallization criterion on the basis of refractive index showed an increasing trend while energy band gap based metallization criterion showed a decreasing trend. The small metallization criterion values of the glass samples represent that the width of the conduction band becomes larger which increase the tendency for metallization of the glasses. The results obtained indicates that the fabricated glasses have high potential to be applied on optical limiting devices in photonic field.